Adsorption of Methane on Poly Vinyl Alcohol (Journal of the College of Basic Education, 2023)
The adsorption studies of methane as environmental pollutant gas on PVA surface was discussed as one of the gas-solid application and removed it from the atmosphere .The adsorption ability of the methane gas at temperature rate 20 , 30, 40 and 50 o C was investigated .The results revealed that the relation between the gas concentration versus adsorption capacity obeys Freundlich isotherm .The a & n values were calculated was increases with the decreases of the temperatures ,this referred that the adsorption was physical adsorption .The adsorption isotherms was investigated from the relation between 1/T versus ln x furthermore the ∆H values was calculated according to Clauses-Clapeyron equation in these range of temperatures.